Telemedicine in Greenland: Citizens' Perspectives. - Nielsen, Lasse O; Krebs, Hans J; Albert, Nancy M; Anderson, Nick; Catz, Sheryl; Hale, Timothy M; Hansen, John; Hounsgaard, Lise; Kim, Tae Youn; Lindeman, David; Spindler, Helle; Marcin, James P; et al. (eScholarship, University of California, 2017)
BackgroundTelemedicine may have the possibility to provide better access to healthcare delivery for the citizens. Telemedicine in arctic remote areas must be tailored according to the needs of the local population. Therefore, we need more knowledge about their needs and their view of telemedicine.ObjectiveThe aim of this study has been to explore how citizens living in the Greenlandic settlements experience the possibilities and challenges of telemedicine when receiving healthcare delivery in everyday life.Materials and methodsCase study design was chosen as the overall research design. Qualitative interviews (n = 14) were performed and participant observations (n = 80 h) carried out in the local healthcare center in the settlements and towns. A logbook was kept and updated each day during the field research in Greenland. Observations were made of activities in the settlements.FindingsData collected on citizens' views about the possibilities of using telemedicine in Greenland revealed the following findings: Greenlandic citizens are positive toward telemedicine, and telemedicine can help facilitate improved access to healthcare for residents in these Greenlandic settlements. Regarding challenges in using telemedicine in Greenland, the geographical and cultural context hinders accessibility to the Greenlandic healthcare system, and telemedicine equipment is not sufficiently mobile.ConclusionGreenlandic citizens are positive toward telemedicine and regard telemedicine as a facilitator for improved access for healthcare in the Greenlandic settlements. We have identified challenges, such as geographical and cultural context, that hinder accessibility to the Greenlandic healthcare system.